Y-2=-1(x+7)

Simple and best practice solution for Y-2=-1(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-2=-1(x+7) equation:


Simplifying
Y + -2 = -1(x + 7)

Reorder the terms:
-2 + Y = -1(x + 7)

Reorder the terms:
-2 + Y = -1(7 + x)
-2 + Y = (7 * -1 + x * -1)
-2 + Y = (-7 + -1x)

Solving
-2 + Y = -7 + -1x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + Y = -7 + 2 + -1x

Combine like terms: -2 + 2 = 0
0 + Y = -7 + 2 + -1x
Y = -7 + 2 + -1x

Combine like terms: -7 + 2 = -5
Y = -5 + -1x

Simplifying
Y = -5 + -1x

See similar equations:

| 4(cos^2(2x))-2=0 | | -25d-50= | | 2990=4*640+6y | | x+y-8x+6y-125=0 | | X-15=-50 | | 70=(4y-30) | | 3x-10y=-22 | | (1-x)+3x=-2(x+1) | | 5x-20+2x+53=180 | | -4z-1=12 | | x+5/x+4=7 | | (-8b)-(-12b)+2=(-10) | | 5x-20+2x-53=180 | | 7b-14= | | 14m-3=12m-15 | | 7t-5t-1=3 | | 2(w+2)=10 | | Y-3=8(x-2) | | 2990=4x+6y | | 3x(8+2)= | | 5p-(-20)-(-11)=(-14) | | 3y+12=27-2y | | 8x^2+36x-288=0 | | (-17j)-2j=(-19) | | 7x^2+2x=3600 | | 32=6p-4 | | 2(u+2)=20 | | 5k-2(k-5)=17 | | X-45=100 | | 14-d=(-4) | | 4(2k-1)=3(K+2) | | (-11j)-(-8j)=(-9) |

Equations solver categories